Characteristics and prognosis of embryonal rhabdomyosarcoma in children and adolescents: An analysis of 464 cases from the SEER database. Issue 4 (28th December 2020) - Wang, Xinyu; Feng, Jun; Li, Zhe; Zhang, Xin; Chen, Jun; Feng, Guoshuang
ABSTRACT: Importance: As the most common subtype of pediatric rhabdomyosarcoma (RMS), the prognosis of embryonal RMS has rarely been investigated solely. Objective: To perform a population‐based study to characterize the prognosis of embryonal RMS in children and adolescents. Methods: Demographic and clinical features were retrospectively evaluated in selected patients with embryonal RMS registered in the Surveillance, Epidemiology, and End Results (SEER) program from 1988 to 2016. Survival curves were compared using the log‐rank test. A multivariate Cox proportional hazards model was developed to assess the impact of each factor on the overall survival. A nomogram was constructed based on the results of Cox regression model. Results: A total of 464 patients were included in the analysis, among which 64.6% were male and 70.2% were white patients. About 38.6% and 26.3% of the patients were at 1–4 years and 5–9 years, respectively. Cox analysis showed that patients at age group 5–9 years had the lowest risk of mortality (hazard ratio [ HR ], 0.277; 95% confidential interval [ CI ], 0.123–0.620), compared with patients diagnosed at less than 1‐year‐old, and age group 1–4 years had the second‐best prognosis. Patients having distant tumors had significantly higher mortality risk ( HR, 4.842; 95% CI, 2.804–8.362) than the patients with localized tumor. Compared with receiving no surgery or radiotherapy, receiving any combination of surgery and radiotherapy would lower the risk of mortality significantly (for surgery without radiotherapy: HR, 0.418; for radiotherapy without surgery: HR, 0.405; and for surgery plus radiotherapy: HR, 0.410). Interpretation: Age, stage at diagnosis, and treatment received were found to be the most important predictors of the overall survival of pediatric embryonal RMS. Abstract : As the most common subtype of pediatric rhabdomyosarcoma (RMS), the prognosis of embryonal RMS has rarely been investigated solely. We utilized SEER database from 1988 to 2016 and assessed the impact of age, sex, race, tumor site, tumor stage, and treatment received on the prognosis of pediatric RMS.